(untitled) (Bangladesh Journal of Urology, 2020)
Seminal vesicle cysts are unusual but treatable causes of lower urinary tract symptoms.Transrectal ultrasonography is a good method for initial evaluation of seminal vesicle cysts. Endorectal magnetic resonance imaging should be reserved for the cases whose ultrasonographic results are not conclusive. Treatment should be restricted to symptomatic patients. Transvesical approach and laparoscopy in the hands of an experienced urologist are the best methods for resection of seminal vesicle cysts. In this article, a case of congenital seminal vesicle cysts is presented and the clinical symptoms, diagnosis, and management are discussed. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.206-209